Feedback Dynamic Algorithms for Preemptable Job Scheduling in Cloud Systems - Li, Jiayin; Qiu, Meikang; Niu, Jianwei; Gao, Wenzhong; Zong, Ziliang; Qin, Xiao (2010 IEEE/WIC/ACM International Conference on Web Intelligence and Intelligent Agent Technology, 2010)
An infrastructure-as-a-service cloud system provides computational capacities to remote users. Parallel processing in the cloud system can shorten the execution of jobs. Parallel processing requires a mechanism to scheduling the executions order as well as resource allocation. Furthermore, a preemptable scheduling mechanism can improve the utilization of resources in clouds. In this paper, we present a preemptable job scheduling mechanism in cloud system. We propose two feedback dynamic scheduling algorithms for this scheduling mechanism. We compare these two scheduling algorithms in simulations. The results show that the feedback procedure in our algorithms works well in the situation where resource contentions are fierce.